2012
DOI: 10.1016/j.mod.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity and branching of embryonic retinal ganglion cell dendrites

Abstract: The shape of a neuron's dendritic arbor is critical for its function as it determines the number of inputs the neuron can receive and how those inputs are processed. During development, a neuron initiates primary dendrites that branch to form a simple arbor. Subsequently, growth occurs by a process that combines the extension and retraction of existing dendrites, and the addition of new branches. The loss and addition of the fine terminal branches of retinal ganglion cells (RGCs) is dependent on afferent input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Here, we aimed to test our previous hypothesis that evoked calcium firing indicated axonal regeneration. To this end, we regulated the calcium responses as well as neural activity via Kir2.1a overexpression (41,(49)(50)(51)(52)(53), PTZ treatment, and scn1a gene knockout (53,54,56). We observed that these effects on regeneration were correlated with neural activity (Figs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, we aimed to test our previous hypothesis that evoked calcium firing indicated axonal regeneration. To this end, we regulated the calcium responses as well as neural activity via Kir2.1a overexpression (41,(49)(50)(51)(52)(53), PTZ treatment, and scn1a gene knockout (53,54,56). We observed that these effects on regeneration were correlated with neural activity (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…To further test our hypothesis that the evoked calcium response indicated intrinsic regenerative ability and study the effect of neural activity on axonal regeneration, we overexpressed Kir2.1a, an inward rectifying potassium channel protein that down-regulates neuronal activity (44,(50)(51)(52), in zebrafish M cells using single-cell electroporation at 4 dpf. We expected that the overexpression of Kir2.1a would influence calcium dynamics by down-regulating neuronal activity.…”
Section: Kir21a Inhibited Neural Activity and Axonal Regenerationmentioning
confidence: 99%
“…Various subtypes of K ir channels have been confirmed to be expressed in RGCs in Xenopus laevis (15) and rats (16,17,22). Specific subunits of K v channels have been observed to be expressed in RGCs in Xenopus laevis (6,15,24,25), goldfish (26), trout (27), mice (28)(29)(30)31), rats (20,32,33) and cats (34). Eag1 and Eag2 have been reported to be expressed in RGCs in rats (21) and cattle (35).…”
Section: Expression Of K + Channels In Rgcsmentioning
confidence: 95%
“…Biochemical, molecular and pharmacological studies have identified numerous types of K + channels in RGCs, including K ir (15)(16)(17), K ATP (18), TASK (19), K v (6,15,20), Eag (21) and K Ca channels (Table I) (22,23). Various subtypes of K ir channels have been confirmed to be expressed in RGCs in Xenopus laevis (15) and rats (16,17,22).…”
Section: Expression Of K + Channels In Rgcsmentioning
confidence: 99%
See 1 more Smart Citation